2015
DOI: 10.1128/cvi.00770-14
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Efficacy of Flagellin-Envelope Fusion Dengue Vaccines in Mice and Monkeys

Abstract: The envelope (E) protein of flaviviruses includes three domains, EI, EII, and EIII, and is the major protective antigen. Because EIII is rich in type-specific and subcomplex-specific neutralizing epitopes and is easy to express, it is particularly attractive as a recombinant vaccine antigen. VaxInnate has developed a vaccine platform that genetically links vaccine antigens to bacterial flagellin, a Toll-like receptor 5 ligand. Here we report that tetravalent dengue vaccines (TDVs) consisting of four constructs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
(69 reference statements)
1
16
0
Order By: Relevance
“…Another promising study reported improved antibody titers (∼60% increase), improved viral neutralization titers (∼3-fold increase), and improved Th1 cytokine profile (∼2-fold increase in IFNγ and TNFα expression) when comparing the effectiveness of flagellin-modified and wildtype porcine circovirus type 2 Cap protein (64). Additionally, many other studies evaluating the effectiveness of recombinantly fusing flagellin to PBV have shown promising results, with the majority reporting improved overall immunogenicity and/or survival when compared to antigen administered alone (65)(66)(67)(68)(69)(70)(71). Unsurprisingly, results like these have propelled multiple flagellin-fused PBVs targeting influenza to clinical trials (72)(73)(74)(75).…”
Section: Genetic Fusion Of Pamp To Pbvmentioning
confidence: 99%
“…Another promising study reported improved antibody titers (∼60% increase), improved viral neutralization titers (∼3-fold increase), and improved Th1 cytokine profile (∼2-fold increase in IFNγ and TNFα expression) when comparing the effectiveness of flagellin-modified and wildtype porcine circovirus type 2 Cap protein (64). Additionally, many other studies evaluating the effectiveness of recombinantly fusing flagellin to PBV have shown promising results, with the majority reporting improved overall immunogenicity and/or survival when compared to antigen administered alone (65)(66)(67)(68)(69)(70)(71). Unsurprisingly, results like these have propelled multiple flagellin-fused PBVs targeting influenza to clinical trials (72)(73)(74)(75).…”
Section: Genetic Fusion Of Pamp To Pbvmentioning
confidence: 99%
“…When expressed as a recombinant polypeptide, EDIII preferentially folds into its native conformation [14] and has been shown to elicit potently neutralizing antibodies that target tertiary epitopes displayed on wild-type virus [15,16]. While DENV EDIII recombinant protein vaccines have been described in the past 10 years, few have undergone immunogenicity trials in non-human primates [1725] with even fewer evaluating protection [18,21,2325]. Those that have been evaluated in protection studies are all EDIII fusion proteins, with EDIII fused to DENV2 capsid protein [18], the P64K protein from N. meningitidis [21,24,25], and Salmonella enterica flagellin [23].…”
Section: Introductionmentioning
confidence: 99%
“…While DENV EDIII recombinant protein vaccines have been described in the past 10 years, few have undergone immunogenicity trials in non-human primates [1725] with even fewer evaluating protection [18,21,2325]. Those that have been evaluated in protection studies are all EDIII fusion proteins, with EDIII fused to DENV2 capsid protein [18], the P64K protein from N. meningitidis [21,24,25], and Salmonella enterica flagellin [23]. Fusion proteins were employed as EDIII carriers that are also immunostimulatory via innate immune pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Tetravalent candidate evaluated in mice; monovalent DV1 and DV2 candidates evaluated in NHPs Hermida et al, 2006;Lazo et al, 2014;Valdés et al, 2009a] EDIII-capsid fusion protein (DIIIC) expressed in E. coli Monovalent DV2 candidate evaluated in NHPs [Gil et al, 2015;Suzarte et al, 2014;Valdés et al, 2009b;Zuest et al, 2015] Tetravalent EDIII-STF2 fusion proteins expressed in E. coli Tetravalent candidate evaluated in mice and NHPs [Liu et al, 2015] EDIII-HBcAg fusion protein expressed in P. pastoris Monovalent DV2 candidate evaluated in mice Recombinant EDII-EDIII-NS1 fusion protein expressed in Drosophila S2 Tetravalent lipidated consensus EDIII (LcED III) expressed in E. coli Tetravalent candidate evaluated in mice [Chen et al, 2013;Chiang et al, 2011;Leng et al, 2009] Lipidated EDIII (LED III) expressed in E. coli Monovalent candidates (DV1,2,4) evaluated in mice [Chiang et al, 2011[Chiang et al, , 2013a MixBiEDIII: bivalent EDIIIs (DV1-2/ DV3-4) expressed in E. coli Tetravalent candidate evaluated in mice [Zhao et al, 2014] Bivalent EDIII (DV1-2) expressed in E. coli Bivalent candidate (DV1-2) evaluated in mice [Zhang et al, 2015] Tetravalent chimeric EDIII expressed in P. pastoris Tetravalent candidate evaluated in mice [Etemad et al, 2008] Non-structural proteins Recombinant DV2 NS1 protein expressed in E. coli Monovalent DV2 candidate evaluated in mice [Amorim et al, 2012] Recombinant DV2 NS1-DEC205 fusion protein expressed in E. coli Monovalent DV2 candidate evaluated in mice [Henriques et al, 2013] Full-length recombinant DV2 NS3 protein expressed in E. coli Monovalent DV2 candidate evaluated in mice [Ramírez et al, 2014] Capsid protein Recombinant capsid protein expressed in E. coli Monovalent DV2 candidate evaluated in mice and NHPs …”
Section: Ediii-p64k Fusion Proteins Expressed In Escherichia Colimentioning
confidence: 99%
“…Other vaccine candidates produced with this platform were well tolerated and immunogenic in humans (Treanor et al, 2010;Taylor et al, 2011) and a fl agellin-based West Nile Virus vaccine protected mice against experimental infection with this virus (McDonald et al, 2007). A tetravalent dengue vaccine candidate was created by replacing the D3 domain of STF2 with the E protein domain III from each DV serotype and fusing an additional copy of the domain III fragment to the C-terminus of STF2 (Liu et al, 2015). Proteins were produced in E. coli.…”
Section: Domain Iii-stf2mentioning
confidence: 99%